Relaciones serológicas entre los Leptodactylus del grupo ocellatus-chaquensis de la cuenca Chaco-paranense y la forma macrosternum - Cei, José Miguel Alfredo María (1970)
Serologic relationship between Leptodactyius of the group ocellatus-chaquensis from the Chaco-paranense basin and the macrosternum form. The allo-sympatric specific complex of Leptodactyius ocellatus-chaquensis-macrosternum is discussed. Serological evidence supports a clear cut specific status of both chaquensis and macrosternum frogs versus ocellatus, in accordance with their faint morphological characters.